An exploratory dosimetric and treatment-time analysis of tangent-arc and continuous semi-arc VMAT in deep inspiration breath-hold radiotherapy for stage I left-sided breast cancer - Yucheng Li; Yinan Chen; Chaoqing Xu; Wenming Zhan; Kainan Shao; Yongshi Jia; Haibo Zhang; Lingyun Qiu; Jieni Ding; Weijun Chen (PLoS ONE, 2026)
Background The use of the deep inspiration breath-hold (DIBH) technique reduces cardiac and lung radiation exposure during left breast cancer radiotherapy. However, the optimal beam delivery technique and the effects of patient adaptation during DIBH remain incompletely understood. Objective In this study, the dosimetric differences between continuous semi-arc and tangent-arc plans in stage I left-sided breast cancer patients using DIBH were compared, and the treatment session duration was descriptively analyzed to characterize treatment-time trends during routine DIBH delivery. Methods Twenty patients treated at our hospital from 01/05/2022–31/05/2023 were retrospectively selected from the institutional database for exploratory dosimetric analysis. Two radiotherapy plans were created on the basis of each patient’s computed tomography (CT) images. Dosimetric parameters for the planning target volume (PTV) and organs at risk (OARs), and beam-on and total treatment times, were compared. Results The conformity index (CI) for the PTV was significantly better with the continuous semi-arc plan ( P < 0.05), whereas the other PTV parameters did not significantly differ between the plans ( P > 0.05). The doses and beam-on time for all OARs (except the left ventricle) were significantly lower for the tangent-arc plan ( P < 0.05). Treatment time tended to stabilize across fractions, with a significant difference between the 15th and 16th sessions ( P < 0.05). Conclusion With the tangent-arc plan, the beam-on time and radiation exposure to OARs were observed to be lower, while adequate PTV coverage was maintained in patients with stage I left-sided breast cancer using DIBH. Treatment times tended to stabilize with increasing treatment fractions. This observation suggests gradual patient adaptation during routine DIBH rather than a predefined training effect. Given the exploratory nature of these findings and the limited sample size from a single institution, these findings should be interpreted with caution and warrant further investigation in larger, multicenter studies.